1978
DOI: 10.1104/pp.62.4.665
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Uptake of Nitrate and Ammonium by Rice Seedlings

Abstract: The uptake of nitrate and ammonium by rice (Oryza sativa) seedlings was compared under various conditions. Nitrate uptake showed a 1-hour lag phase and then a rapid absorption phase, whereas ammonium uptake showed passive absorption during the first hour, then a shoulder of absorption, followed by a rapid metabolism-dependent absorption phase. Light did not affect the uptake of nitrate or ammonium. The uptake of nitrate and ammonium was markedly suppressed by removal of the endosperm. After removal of the endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(42 citation statements)
references
References 9 publications
0
39
0
Order By: Relevance
“…For optimal grain yield, paddy rice farming requires extensive watering (flooded by rivers and rainfall during the monsoon season, or by irrigation) for three quarters of the growing season, which influences the availability of the macronutrient nitrogen (N) in the soil. In non-aerated paddy fields, rice mobilizes ammonium (NH 4 + ) rather than nitrate (NO 3 − ) as the preferred N source (Fried et al 1965;Sasakawa and Yamamoto 1978). Yet, plant growth, yield and N-use efficiency are significantly enhanced when NH 4 + and NO 3 − are provided simultaneously (Kronzucker et al 1999;Kronzucker et al 2000;Duan et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For optimal grain yield, paddy rice farming requires extensive watering (flooded by rivers and rainfall during the monsoon season, or by irrigation) for three quarters of the growing season, which influences the availability of the macronutrient nitrogen (N) in the soil. In non-aerated paddy fields, rice mobilizes ammonium (NH 4 + ) rather than nitrate (NO 3 − ) as the preferred N source (Fried et al 1965;Sasakawa and Yamamoto 1978). Yet, plant growth, yield and N-use efficiency are significantly enhanced when NH 4 + and NO 3 − are provided simultaneously (Kronzucker et al 1999;Kronzucker et al 2000;Duan et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore not surprising that NH % + nutrition, as opposed to NO $ − nutrition, has received almost exclusive attention in rice (Bonner, 1946 ;Fried et al, 1965 ;Shen, 1969 ;Wang et al, 1993). However, some reports have indicated that rice does possess some capacity for root NO $ − absorption (Ismunadji & Dijkshoorn, 1971 ;Sasakawa & Yamamoto, 1978 ;Youngdahl et al, 1982 ;Raman et al, 1995) and for the reduction of NO $ − in leaves (Tang & Wu, 1957). Isolated nursery trials have shown that NO $ − pretreatment of rice seedlings can result in enhanced transplanting success (Yamasaki & Seino, 1965), and, perhaps most strikingly, several varieties of Indica rice have been shown to exhibit superior growth on NO $ − under certain conditions (Ta & Ohira, 1981 ;.…”
Section: mentioning
confidence: 99%
“…In the transplanting system, including manual transplanting and mechanical transplanting, rice seedling development is generally delayed due to injuries to the root caused by uprooting and replanting (Salam et al, 2001). Furthermore, the balance between water and transpiration in seedlings also changes, causing the leaves to wilt or partly die (Sasakawa and Yamamoto, 1978). Therefore, the growth and development of the seedlings become stagnant temporarily; this is the so-called "transplanting shock" (Sasakawa and Yamamoto, 1978;Salam et al, 2001).…”
mentioning
confidence: 99%
“…Furthermore, the balance between water and transpiration in seedlings also changes, causing the leaves to wilt or partly die (Sasakawa and Yamamoto, 1978). Therefore, the growth and development of the seedlings become stagnant temporarily; this is the so-called "transplanting shock" (Sasakawa and Yamamoto, 1978;Salam et al, 2001). In the seeding broadcasting system, seedlings are grown in a nursery or plate, and at 15 − 20 days old, they are broadcast manually to the puddled field.…”
mentioning
confidence: 99%